Dampak Gadget terhadap Perkembangan Remaja Awal Studi Kasus Siswa Sekolah Menengah Pertama Negeri 2 Bengkalis - Titin Sumarni; Mufaro'ah Mufaro'ah; Irlina Dewi (STAIN Bengkalis, 2020)
This study aims to determine the function of the gadget, the direction of the use of the gadget, the factors of gadget use, the method used is descriptive qualitative. Research results 1. Gadget function is that most of the gadgets for communication are around 93.33%, while the remaining 6.67% are very varied, such as to add insight, entertainment, lifestyle, business places and some who use gadgets for things. which is a threat to him. 2. Factors that influence the development of early adolescents are internal factors (creativity, ability, intelligence, talents and interests), external factors (parenting style, school environment, peers, society, geography). 3. Efforts to direct the positive functions of gadgets, namely a. not allowed to use gadgets at school, b. Can bring gadgets or laptops during IT learning, c. There is supervision and control from parents in using gadgets. 4. The effect of the use of gadgets is that there is no significant effect on the development of adolescents, especially students of grade 1 SMPN 2 Bengkalis with a correlation value of 0.46%, which means that there is no effect of gadgets on the development of adolescents, especially in terms of religious, secondary school, behavior and attitudes. However, gadgets still affect early adolescents, gadgets are used to communicate. while the development of adolescents, especially the development of religious, secondary sec, behavior and attitudes are influenced by parents, school and friends.